Context-dependent emotional empathy in virtual reality - Kuypers, Kim PC (Advances in Social Sciences Research Journal, 2018)
Empathy has been typically studied by means of paradigms including static representations of socially relevant stimuli and it has been acknowledged that there is need for more ecologically valid, dynamic measures. The present study aimed to study implicit (‘arousal’) and explicit (‘concern’) emotional empathy in response to positive and negative emotional stories in three virtual reality settings in males and females (N=39). It was hypothesized that emotional stories would elicit less arousal or implicit emotional empathy in a nature environment compared to a more urbanized environment. Males were hypothesized to score in general lower on empathy measures. Findings showed that emotional empathy was context-dependent and independent of gender. While it has been shown that environmental presence matters when it comes to emotional empathy, the explanation why this specific behavioral pattern was observed still needs to be clarified and suggestions to extend and improve the Virtual Reality Empathy Paradigm have been suggested.